2008
DOI: 10.1128/aac.01410-07
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin Exerts Bactericidal Activity without Lysis of Staphylococcus aureus

Abstract: The ability of daptomycin to produce bactericidal activity against Staphylococcus aureus while causing negligible cell lysis has been demonstrated using electron microscopy and the membrane integrity probes calcein and ToPro3. The formation of aberrant septa on the cell wall, suggestive of impairment of the cell division machinery, was also observed.Many antibiotics derive bactericidal activity from their ability to lyse cells, which may cause liberation of potent proinflammatory bacterial components, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
99
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 12 publications
10
99
0
Order By: Relevance
“…Studies using both scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicate that daptomycin does not cause cell lysis of S. aureus and E. faecalis, although some morphological changes are observed. 76,77 With Staphylococcus aureus in liquid culture, daptomycin at 4 µg/ml produced a 10 3 -fold decrease in cell viability with no concomitant drop in optical density. 76 Electron microscopy showed that the cells remained intact, and the cell membranes free of discontinuities, but formation of aberrant division septa was common.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies using both scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicate that daptomycin does not cause cell lysis of S. aureus and E. faecalis, although some morphological changes are observed. 76,77 With Staphylococcus aureus in liquid culture, daptomycin at 4 µg/ml produced a 10 3 -fold decrease in cell viability with no concomitant drop in optical density. 76 Electron microscopy showed that the cells remained intact, and the cell membranes free of discontinuities, but formation of aberrant division septa was common.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectmentioning
confidence: 99%
“…76,77 With Staphylococcus aureus in liquid culture, daptomycin at 4 µg/ml produced a 10 3 -fold decrease in cell viability with no concomitant drop in optical density. 76 Electron microscopy showed that the cells remained intact, and the cell membranes free of discontinuities, but formation of aberrant division septa was common. When the cells were loaded with calcein, an anionic fluorescent small molecule, the dye was retained after exposure to daptomycin even after the cells had lost viability.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectmentioning
confidence: 99%
See 3 more Smart Citations